10 Gbit s−1 Free Space Data Transmission at 9 µm Wavelength With Unipolar Quantum Optoelectronics (Laser Photonics Rev. 16(2)/2022). Issue 2 (5th February 2022) - Dely, Hamza; Bonazzi, Thomas; Spitz, Olivier; Rodriguez, Etienne; Gacemi, Djamal; Todorov, Yanko; Pantzas, Konstantinos; Beaudoin, Grégoire; Sagnes, Isabelle; Li, Lianhe; Davies, Alexander Giles; Linfield, Edmund H.; et al.
Abstract : Stark Effect Modulator Carlo Sirtori and colleagues present a high frequency Stark effect modulator in article number 2100414, which writes data‐bits on a laser beam by shifting the absorption of an optical transition in and out of the laser frequency. Paired with a quantum cascade detector they form a free space optical link allowing for 10Gbit s −1 data transmission at room temperature before any equalization.